Comparative Analysis of Construction Costs for Concrete and Steel: A Case Study of the Modern Islamic Boarding School an – Nizam Purwokerto - Hanapi, Fajri; Rafli, Mochamad; Jati, Muhamad Alfito; Farhan, Ohan (PT FORMOSA CENDEKIA GLOBAL, 2025)
The selection of structural materials plays a crucial role in determining cost efficiency and construction time in building construction projects. This study aims to analyze and compare the construction costs of reinforced concrete and steel structures in the construction of the Modern Islamic Boarding School An-Nizam in Purwokerto. A quantitative comparative method was used by calculating the volume of work, construction cost estimates (RAB), and project duration for both types of structures. The analysis focused on main structural elements such as columns and beams, based on detailed drawings, unit price standards, and project technical data. Based on the calculations and analysis of this project, it can be concluded that the total construction cost for the reinforced concrete structure is Rp 8,983,363,148.58. Meanwhile, the total construction cost for the steel structure is Rp 8,445,489,989.60. The duration of the steel construction work is 19-20 weeks, and the duration of the concrete structure construction work is 25-30 weeks. Therefore, it can be concluded that from this case study, the total cost required for concrete structure construction is cheaper than steel structure construction by a difference of Rp 537,873,158.98. However, the duration of steel structure construction is faster than concrete construction, with a difference of 6-10 weeks.